Opportunities for the inclusion of less-favoured areas in the Northern Great Plain region - Bittner , Beáta (Applied Studies in Agribusiness and Commerce, 2007)
Agricultural economics and its part, rural economics plays a determining role in Hungary. Most rural families perform self-sufficient farm production for a living. In the present conditions of infrastructure and human resources, there are regions where the only rural alternative for employment is agriculture. There are significant differences among the regions considering natural resources and equipment available for farm production, and these differences affect potential income (Vöröset al. 1999). The primary aim of the European Union is to reduce such differences among the regions.The new research program of the University of Debrecen tackles the fundamental questions of regional development through the research and management of social asymmetries by using economic and other relevant tools. This program also provides suggestions for facilitating the development of less-favoured areas.